Pengembangan Sistem Kontrol Mesin Pengering Kopi Berbasis Multiple Sensor - Estria Devi Rivana (Fakultas Teknologi Pertanian, 2025)
Drying is a crucial stage in the post-harvest processing of coffee beans, to determines the aroma, flavor, and shelf life of the final product. In Indonesia, traditional sun-drying methods are still widely used despite their limitations, such as dependence on weather conditions and the inability to accurately control temperature and humidity. This study aimed to develop a coffee bean drying machine equipped with multiple sensors to monitor and control drying parameters in real time, thereby improving efficiency and drying quality. The machine is equipped with a DHT22 sensor to measure ambient temperature and humidity, as well as a GY906 thermal sensor to non-invasively detect the surface temperature of the coffee beans. Testing was conducted over 120 minutes using Arabica coffee beans, with moisture content monitored using a moisture meter. The results showed a final moisture content of 11.5%, which meets the national standard (11–12%), with the drying rate decreasing from 0.5% to 0.1%. The automatic control system based on Arduino Uno proved effective in maintaining optimal drying conditions, improving energy efficiency, and reducing drying time. Therefore, this machine offers an innovative solution for coffee farmers to improve the quality and competitiveness of Indonesian coffee products.
Reuploud Repository hasyim Juni 2026 :: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Coffee dryer; Multiple sensors; Moisture meter; Temperature and Humadity